PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. SELAT BUTON - Katjina, Husnah; Jasiyah, Rabiyatul; Suriadi, Suriadi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the effect of work discipline and work motivation on employee performance at PT Selat Buton. The sample in this study consisted of 38 employees of PT Selat Buton. This research employed a descriptive quantitative method. Data were collected using questionnaires, with responses measured using a Likert scale. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that work discipline has a significant effect on employee performance at PT Selat Buton. The t-test results show that work motivation significantly influences employee performance, with a t-value of 3.149, which is greater than the t-table value of 1.688, and a significance level of 0.003, which is lower than 0.05 (0.003 < 0.05). In addition, the t-test results demonstrate that work discipline significantly affects employee performance, with a t-value of 6.637, which is greater than the t-table value of 1.688, and a significance level of 0.000, which is lower than 0.05 (0.000 < 0.05). Furthermore, the F-test results show that work discipline and work motivation simultaneously have a significant effect on employee performance, with an F-value of 22.147, which is greater than the F-table value of 3.27, and a significance level of 0.000, which is lower than the confidence level of 0.05. Therefore, the hypotheses proposed in this study are accepted.